3(x+1)=34(x+23)

Simple and best practice solution for 3(x+1)=34(x+23) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(x+1)=34(x+23) equation:


Simplifying
3(x + 1) = 34(x + 23)

Reorder the terms:
3(1 + x) = 34(x + 23)
(1 * 3 + x * 3) = 34(x + 23)
(3 + 3x) = 34(x + 23)

Reorder the terms:
3 + 3x = 34(23 + x)
3 + 3x = (23 * 34 + x * 34)
3 + 3x = (782 + 34x)

Solving
3 + 3x = 782 + 34x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-34x' to each side of the equation.
3 + 3x + -34x = 782 + 34x + -34x

Combine like terms: 3x + -34x = -31x
3 + -31x = 782 + 34x + -34x

Combine like terms: 34x + -34x = 0
3 + -31x = 782 + 0
3 + -31x = 782

Add '-3' to each side of the equation.
3 + -3 + -31x = 782 + -3

Combine like terms: 3 + -3 = 0
0 + -31x = 782 + -3
-31x = 782 + -3

Combine like terms: 782 + -3 = 779
-31x = 779

Divide each side by '-31'.
x = -25.12903226

Simplifying
x = -25.12903226

See similar equations:

| 3(1-2x)+12=10-2(x-39) | | 3/8-3/4=x | | 9s^2-24s+16= | | 24x-4-8x+26=15x+25 | | 5t-8=-28+t | | x^2-4x+1=5 | | 8.2x-2.3x=-94.4 | | 6x^3+10x^2+21x-35=0 | | (4a^3-4a^2)+(6a^3+5a^2)=0 | | 9s^2+24s+16= | | 3x-(-2x+2)=6-(2x-4) | | 3y-(2y-4)=5y | | 12+0.35=20.05 | | 25a^4b^7c^9-75a^8b^9c^10= | | 23.1z=46.2 | | n^2-18n-13=6 | | (x+2)*3=(13-x)*4+3 | | 5a+6b-16=0 | | 5y=(3y-5) | | 4d^2+4d+100= | | (7t-1)-(8t+5)= | | (4b-4)(5b-6)= | | 5*(3.2-1.2B)+6B=16 | | 4y-2= | | -3y-4y(2+y)= | | (7x^2-x-2)-(-6x^3+3)= | | -2=4x+6+4 | | x*x*x-(2x^2+4)= | | -3(3r-8)=-36 | | -2=4+6+4 | | x^2+6x+42=0 | | (m^2-m-4)+(m-5)= |

Equations solver categories